2019
DOI: 10.3390/v12010015
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Promotes Porcine Parvovirus Replication and Induces Non-Apoptotic Cell Death in Porcine Placental Trophoblasts

Abstract: Autophagy plays important roles in the infection and pathogenesis of many viruses, yet the regulatory roles of autophagy in the process of porcine parvovirus (PPV) infection remain unclear. Herein, we show that PPV infection induces autophagy in porcine placental trophoblasts (PTCs). Induction of autophagy by rapamycin (RAPA) inhibited the occurrence of apoptotic cell death, yet promoted viral replication in PPV-infected cells; inhibition of autophagy by 3-MA or ATG5 knockdown increased cellular apoptosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…P1400, Solarbio, CHN) at 37 °C in an incubated with 5% CO 2 atmosphere. PPV China-XY strain (MK993540) was propagated as previously described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P1400, Solarbio, CHN) at 37 °C in an incubated with 5% CO 2 atmosphere. PPV China-XY strain (MK993540) was propagated as previously described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…AMPK is a negative regulator of mTORC1, which can suppress mTORC1 by activating tuberous sclerosis complex 2 (TSC2) or phosphorylating the regulatory-associated protein of mTORC1 (Raptor) [ 21 , 22 ]. Our recent study showed that PPV infection induces autophagy in PTCs [ 23 ]. Therefore, we were interested in determining whether mTORC1 is involved in PPV-induced autophagy and whether PPV-induced autophagy occurs via an AMPK-dependent mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Specific siRNAs used to silence Akt, p38 MAPK, JNK, ERK, AMPK, PKCδ were referred to in our previous study[ 36 , 63 ]. HDAC6 (GenBank: XM_003360315.5) and AMPK (GenBank: NM_001167633.1) siRNAs were designed (HDAC6 siRNA: 5′-GGAGGAGCUUAUGUUGGTT-3′; AMPK siRNA: 5′-GCUUGCCAAAGGAAUGATT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…PPV XY strain (Genbank: MK993540) was propagated in PK-15 cells. The crude PPV preparation was purified using ultracentrifugation over sucrose cushions (2 mL of 50% sucrose plus 2 mL of 20% sucrose) by Optima XPN-100 Ultracentrifugation with a SW 41 Ti rotor, at 200 000 g for 2 h. Virus titers in the culture supernatants were determined by the Reed-Muench method [ 28 ].…”
Section: Methodsmentioning
confidence: 99%